﻿Turismo de eventos como estratégia no combate à sazonalidade: uma análise na hotelaria de Natal - RN - Medeiros, Andressa Andrade de (2007)
The aim of this work is to analyse the tourism events and the performance of this segment from market as strategy in the combat of Natal's hotel seasonality, in the executives/managers's vision from this sector. Two searches were realized to turn available this study: Inicialy a bibliographic search involving the concepts associated with the tematic in question so that it arranges the embasament theoric-scientific and a survey from facts through the country search, where it was applicable in the establishments of work's population with the auxiliary from a formulary answered by a personal interview. The analyses techniques through facts were: estatistic descritive and Kolmogorov-smirnov test.Among the results found, it was verified that the main reasons alleged by the hotels to ingress in the segment from the events were the alinement from the competitive company, the diversification in the options in the sense of occupy the establishments during the period of low season and answer to the demand of market. Investigated the profile from the events occured in the Natal hotels referring to the port, public origin , kinds of events and frequency from their realizations, as well as , the capacity from these establishments to attend this segment.It was noticed that in spite of the hotels agree that the events are important estrategies to combat the seasonality, the establishments still suffer with the flutuation, what can be justified from the moment that it's considered that the events also behave from seasonal manner, having more concentration in certain periods from the year. It was evaluated that the main advantage noticed by the realization from the hotels's events is the utilization from alimentation and drinking services, surpassing the advantage from elevation of taxes occupation from the apartments